2020
DOI: 10.1111/all.14236
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide/sphingosine‐1‐phosphate imbalance is associated with distinct inflammatory phenotypes of uncontrolled asthma

Abstract: Background: Asthma is associated with inflammatory dysregulation, but the underlying metabolic signatures are unclear. This study aimed to classify asthma inflammatory phenotypes based on cellular and metabolic features. Methods: To determine cellular and metabolic profiles, we assessed inflammatory cell markers using flow cytometry, sphingolipid (SL) metabolites using LC-MS/MS, and serum cytokines using ELISA. Targeted gene polymorphisms were determined to identify genetic predispositions related to the asthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 57 publications
0
49
2
Order By: Relevance
“…81 The increased serum IL- 33 The DP2 receptor is an essential regulator in allergic asthma because it can be activated by both allergic and nonallergic stimuli. 88 The activation of the DP2 receptor pathway increases both 89 Kim et al 90 showed that the ceramide/sphingosine-1-phosphate ratio can discriminate between two different asthma endotypes. however, it did not have an impact on the differentiating of other CD4+ T-cell subsets.…”
Section: Novel Molecules and Pathwaysmentioning
confidence: 99%
“…81 The increased serum IL- 33 The DP2 receptor is an essential regulator in allergic asthma because it can be activated by both allergic and nonallergic stimuli. 88 The activation of the DP2 receptor pathway increases both 89 Kim et al 90 showed that the ceramide/sphingosine-1-phosphate ratio can discriminate between two different asthma endotypes. however, it did not have an impact on the differentiating of other CD4+ T-cell subsets.…”
Section: Novel Molecules and Pathwaysmentioning
confidence: 99%
“…Ceramides in bronchoalveolar lavage fluid have been reported to be associated with airway inflammation and hyperreactivity in mouse models of house dust mite-induced asthma and neutrophil elastase [14,28]. A recent study demonstrated that the serum levels of ceramides were higher in asthmatic patients than in healthy controls and in asthmatic patients in an uncontrolled than in a controlled state [30]. Untargeted and targeted metabolomics study that aimed to determine different metabotypes according to asthma severity revealed that the serum levels of S1P, sphingosine and ceramides were high in severe asthmatics [31].…”
Section: Plos Onementioning
confidence: 99%
“…Despite accumulating evidence for the recycling synthetic pathway of sphingolipids [13,14,16,28,30,31], there are scanty data on the role of the de novo synthetic pathway of sphingolipids in asthma pathogenesis [29]. The pathogenic role of the de novo synthetic pathway has been suggested from the GWAS studies showing that ORMDL and CerS2 were significantly associated with the risk of asthma [21,22,32,33].…”
Section: Plos Onementioning
confidence: 99%
“…Ceramide is significantly increased in the lungs and serum of patients with asthma and COPD [ 14 , 15 ]. Ceramide is also associated with the phenotypes of asthma and COPD, and may contribute to exacerbation and poor disease control by worsening airway inflammation [ 16 , 17 ]. Studies by Oyeniran et al showed that intratracheal delivery of ceramide in mice promoted pulmonary inflammation and tissue remodeling, and caused airway flow obstruction [ 18 ].…”
Section: Introductionmentioning
confidence: 99%